Spectroscopic characteristics of Ca2Al2SiO7 phosphors co-doped with Ce3+ and Sm3+ - Tiến, Đỗ Thanh; Nguyễn , Mạnh Sơn; Trần , Thương Thiên (Hue University Journal of Science: Natural Science, 2022)
Luminescent materials Ca2Al2SiO7 co-doped with Ce3+ and Sm3+ were prepared with the solid-state reaction method. The XRD diffraction patterns show that the samples have a single tetragonal phase structure. The luminescent spectra of Ca2Al2SiO7: Ce3+,Sm3+ phosphor have a broad band with a peak at 420 nm, characterizing the transition of the electronic configuration of Ce3+ ion and narrow lines peaked at about 563, 602, 645, and 712 nm, representing the transition of the Sm3+ ion. The energy transfer from Ce3+ to Sm3+ was presented and discussed.